A new technique to prevent curling of guide wire in urinary bladder during J stent insertion with flexible cystoscope - Mahmood, Nasir; Pasha, Tahir (Canadian Urological Association Journal, 2016)
Insertion of J stent is a very common procedure performed by urologists. This procedure is often performed to relieve ureteral obstruction due to stones, tumours, ureteral kink, or stricture on urgent basis. An increasing number of urologists are using a flexible cystoscope and local anaesthetic for J stent insertion. Occasionally, the guide wire curls in the bladder, making it impossible to insert the J stent. Here, we describe a simple method to overcome this problem using modified ureteral dilator, which is usually available in the cystoscopy suite.